2016
DOI: 10.1515/pjvs-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of immune organs after very virulent plus strain of Marek’s disease virus infection in vaccinated hens

Abstract: Marek's disease (MD) outbreaks in poultry flocks may be associated with overriding of vaccine immune protection by very virulent (vvMDV) or very virulent plus (vv+MDV) strains. This paper presents the study on lymphoid organ morphology in the latent phase of MD caused by vv+MDV which break post-vaccinal protection in hens. We also immunohistochemically examined B and T populations as well as B/T and CD4 + /CD8+ ratio of lymphocytes in lymphatic organs and, as a background, in MD lymphomas from non-lymphatic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore, it is believed that the wide use of MDV vaccines is driving the evolution of MDV field viruses toward greater virulence [1,[11][12][13][14]. Indeed, virulent or very virulent plus MDV (vv+ MDV) field strains were documented to break through the protection conferred by CVI988 vaccine clinically or experimentally [14][15][16][17][18], highlighting a worry of the lack of a better alternative to CVI988 to combat increasingly virulent MDV strains in the future. Unfortunately, progress in developing such vaccines has been slow, since most MDV vaccines under development are no more efficacious or safer than CVI988 [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is believed that the wide use of MDV vaccines is driving the evolution of MDV field viruses toward greater virulence [1,[11][12][13][14]. Indeed, virulent or very virulent plus MDV (vv+ MDV) field strains were documented to break through the protection conferred by CVI988 vaccine clinically or experimentally [14][15][16][17][18], highlighting a worry of the lack of a better alternative to CVI988 to combat increasingly virulent MDV strains in the future. Unfortunately, progress in developing such vaccines has been slow, since most MDV vaccines under development are no more efficacious or safer than CVI988 [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous reports have shown that molecular evolution of MDV genes could increase the pathogenicity of MDV virulent strains [ 34 ]. Infection of very virulent MDV (vvMDV) could also break post-vaccinal protection and cause the outbreak of MDV [ 35 ]. Therefore, the safety of this measurement needs to be studied in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Although MD vaccines have successfully been used in reducing major losses due to the disease, several factors such as improper use of the vaccine, exposure to virulent viruses before the development of immunity, interference from maternally derived antibodies and emergence of new virulent strains have limited the effectiveness of the vaccines. In fact, MDV has evolved into a more virulent form and the emerging strains not only are capable of breaking vaccine immunity but also show immunosuppressive effects [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%